Computer-guided identification of novel inhibitors of apoptosis-signaling kinase 1 from Spondia mombim bioactive compounds against colorectal cancer - Olusola Olalekan Elekofehinti; Hannah Oluwaseun Popoola; Adedotun Olayemi Oluwatuyi; Opeyemi Iwaloye; Moses Orimoloye Akinjiyan; Oluwamodupe Cecilia; Frank Abimbola Ogundolie; Olalekan Isaac Olatunde; Oussama Abchir; Samir Chtita; Joao Batista Texeira Rocha (Egyptian Journal of Medical Human Genetics)
Abstract Background Apoptosis-signaling kinase 1 is a MAPKKK (mitogen-activated protein kinase) overexpressed in various types of human cancer including colorectal cancer. It mediates inflammation and apoptosis and promotes cell proliferation through the transcription of cyclin D1. 5-Fluorouracil remains one of the primary recommended drugs to manage colorectal cancer. However, this drug often causes various adverse effects, notably diarrhea, vomiting, nausea, and leukopenia. Therefore, a novel treatment is required to eradicate these problems. The clinical implication of apoptosis-signaling kinase 1 in the pathogenicity of colorectal cancer makes it an important drug target in the treatment of colorectal cancer. The use of natural compounds in human cancer treatment continues to gain significant attention in the scientific community due to their therapeutic efficacy. Method In this study, computational models such as flexible docking, induced fit docking, and binding free energy calculation were employed to identify small molecule inhibitors from known bioactive compounds of Spondias mombin in reference to 5-fluorouracil (Colorectal cancer standard drug) targeting apoptosis-signaling kinase 1. Results Molecular docking studies identified 10 promising candidates which include uvaretin, rutin, isoquercitrin, ellagic acid, quercetin, linalool, acetyl eugenol, tangeretin (-)-catechin, and d-sorbitol based on their favorable binding affinity, with uvaretin having the best score (− 11.328 kcal/mol). The results were further validated with more dependable analysis such as induced fit docking and binding free energy calculation. These compounds showed modest indices for ADMET parameters. Molecular dynamic simulation validated ellagic acid and (-)-catechin with greater binding stability as leading compounds. Conclusion These compounds showed improved flexible docking results and formed considerable stable interaction with the protein than 5-fluorouracil. They are non-carcinogenic. The oral bioavailability and toxicities of these compounds are promising as compounds obeyed the Lipinski rule of five. The constructed quantitative structure–activity relationship model with a trustworthy R 2 coefficient value supports the inhibition prowess of these compounds. The findings from this research confer that these compounds could be considered potent apoptosis-signaling kinase 1 inhibitors, and these could be confirmed experimentally as lead compounds of apoptosis-signaling kinase 1 inhibitors in colorectal cancer.